Konsep Wilayatul Hisbah Menurut Imam Al-Mawardi - Sayuti Sayuti (Ma'had Aly Raudhatul Ma'arif, 2024)
This study discusses Wilayatul Hisbah in Islam, an institution tasked with enforcing Islamic law by commanding good and preventing evil, in accordance with the principle of amar ma'ruf nahi mungkar outlined in the Qur'an. This institution has existed since the early days of Islam and has evolved within the structure of Islamic governance, from the time of the Prophet Muhammad (SAW) to the Ottoman Caliphate. However, the concept and implementation of Wilayatul Hisbah have been the subject of debate, particularly regarding its purpose and role in safeguarding religious values. Scholars such as Imam al-Mawardi and Ibn Taymiyyah have differing views on the aims and functions of Hisbah in Islamic society. This research employs historical and comparative analysis methods to understand how Wilayatul Hisbah has adapted to changes in time and culture, and to explore the divergent opinions among scholars regarding its scope and authority. Based on the research, Imam al-Mawardi in his book al-Ahkam al-Sulthaniyyah states that the concept of Hisbah is identical to the principle of amar ma'ruf nahi mungkar, focusing on actions that disturb public order. The Muhtasib, as the executor of Hisbah, is tasked with handling violations of public order and morality, and acts as a special court. Imam al-Mawardi categorizes the duties of Hisbah into amar ma'ruf (commanding good) and nahi mungkar (preventing evil), which includes rights of Allah, human rights, and a combination of both. Wilayatul Hisbah is seen as an institution that exists between the judge and the head of criminal affairs in maintaining social order based on Islamic principles.